Natural fibre-reinforced thermoplastic composites from woven-nonwoven textile preforms: Mechanical and fire performance study - (:unkn) unknown (ELSEVIER SCI LTD, 2018)
Partially and fully biodegradable natural fibre reinforced composites have been prepared using a novel patented woven-nonwoven technology. Natural fibres included jute and sisal, whereas the matrices were of synthetic polymers derived from petroleum (polypropylene (PP)) or natural (polylactic acid (PLA)) resources. The physical, mechanical and flammability properties of these partially and fully biodegradable composites have been studied and compared with those of similarly produced glass-fibre reinforced PP and PLA composites with a view to enabling their use in automotive applications. Mechanical test results showed that the tensile and flexural moduli of the PLA composites were higher than respective PP composites. In comparison, sisal composites have higher tensile and flexural moduli than jute composites. The fire performance of the composites studied by cone calorimetry showed that while natural fibre reinforcement had no effect on time-to-ignition, peak heat release was significantly reduced. PLA composites had lower burning propensity compared to respective PP composites.
Keywords: Polymer-matrix composites (PMCs); Fabrics/textiles; Preforms; Mechanical properties; Fire performances; BIODEGRADABLE POLYMERS; BIOCOMPOSITES; POLYPROPYLENE; FLAMMABILITY; RETARDANCY